Tokoh Wanita Di Jawa Sekitar Abad VII - XIV Masehi - Rita Istari (Berkala Arkeologi, 2004)
Since the seventh century AD, when Indonesia was still a kingdom, especially on the island of Java, women have been considered able to rule and run the government. Their position as leaders has earned the trust of its people who have wholeheartedly obeyed the rules decided by their leaders. Similarly, a woman as the king's companion actively helps her husband in running the government with the various advantages he has. Historical evidence indirectly acknowledges to women that the position of women is not always subordinate to that of men. Their competence and ability in running the government with wise actions and decisions has proven it.